The Promise and Pitfalls of Gender Mainstreaming - Sainsbury, Diane; Bergqvist, Christina (International Feminist Journal of Politics, 2009)
This article examines gender mainstreaming in Sweden, which is an interesting case because several favorable conditions make its implementation likely. It addresses two main questions: (1) to what extent has gender mainstreaming been implemented and (2) what are the consequences? The article first discusses the pros and cons of gender mainstreaming as reflected in the international feminist debate. It then briefly describes the favorable conditions of the Swedish case and subsequently maps out the introduction of gender mainstreaming since 1994, focusing on the process and its politics. It concludes with a discussion of the Swedish experience in terms of the promise and pitfalls of gender mainstreaming identified in the feminist debate and the implications of the Swedish case for feminist theorizing on gender mainstreaming.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616740902789575
Keywords: Sweden; feminist theory; gender equality policies; gender mainstreaming; gender politics

The Aftermath of Feminism: Gender, Culture and Social Change - McRobbie, Angela (SAGE Publications, 2009)
Congratulations to Dr. McRobbie! This book has been named to the list of books for the 2009 Critics Choice Book Award of the American Educational Studies Association (AESA).These essays show Angela McRobbie reflecting on a range of issues which have political consequence for women, particularly young women, in a context where it is frequently assumed that progress has been made in the last 30 years, and that with gender issues now 'mainstreamed' in cultural and social life, the moment of feminism per se is now passed. McRobbie trenchantly argues that it is precisely on these grounds that invidious forms of gender -re-stabilisation are able to be re-established. Consumer culture, she argues, encroaches on the terrain of so called female freedom, appears supportive of female success only to tie women into new post-feminist neurotic dependencies. These nine essays span a wide range of topics, including - the UK government's 'new sexual contract' to young women, - popular TV makeover programmes, - feminist theories of backlash and the 'undoing' of sexual politics, - feminism in a global frame- the 'illegible rage' underlying contemporary femininities.
Google-Books-ID: jmMREuksN10C
Keywords: Social Science / Essays; Social Science / Feminism & Feminist Theory; Social Science / Sociology / General; Social Science / Women's Studies